Beyond sunspots: Studies using the McIntosh Archive of global solar magnetic field patterns. Issue Volume 12:Issue S328(2016) (12th September 2017) - Gibson, Sarah E.; Webb, David; Hewins, Ian M.; McFadden, Robert H.; Emery, Barbara A.; Denig, William; McIntosh, Patrick S.
Abstract: In 1964 (Solar Cycle 20; SC 20), Patrick McIntosh began creating hand-drawn synoptic maps of solar magnetic features, based on Hα images. These synoptic maps were unique in that they traced magnetic polarity inversion lines, and connected widely separated filaments, fibril patterns, and plage corridors to reveal the large-scale organization of the solar magnetic field. Coronal hole boundaries were later added to the maps, which were produced, more or less continuously, into 2009 (i.e., the start of SC 24). The result was a record of ~45 years (~570 Carrington rotations), or nearly four complete solar cycles of synoptic maps. We are currently scanning, digitizing and archiving these maps, with the final, searchable versions publicly available at NOAA's National Centers for Environmental Information. In this paper we present preliminary scientific studies using the archived maps from SC 23. We show the global evolution of closed magnetic structures (e.g., sunspots, plage, and filaments) in relation to open magnetic structures (e.g., coronal holes), and examine how both relate to the shifting patterns of large-scale positive and negative polarity regions.